Acute and Chronic Complications in Patients with Ductal Carcinoma in Situ Treated with Intraoperative Radiation Therapy. Issue 6 (4th August 2016) - Epstein, Melinda S.; Silverstein, Melvin J.; Lin, Kevin; Kim, Brian; De Leon, Cristina; Khan, Sadia; Guerra, Lisa E.; Snyder, Lincoln; Coleman, Colleen; Lopez, January; Mackintosh, Ralph; Chen, Peter
Abstract: Intraoperative radiation therapy (IORT) delivers radiation therapy directly to the tumor bed at the time of surgery. Minimal data are available regarding IORT complications in patients diagnosed with ductal carcinoma in situ (DCIS) using the Xoft ® Axxent eBx ® System. 146 patients with pure DCIS received X‐ray based IORT therapy using the Xoft ® Axxent eBx ® System at Hoag Memorial Hospital Presbyterian between June 2010 to April 2016 and were accrued to an IORT data registry study. The protocols were approved by the institutional review board and met the guidelines of their responsible governmental agency. Data were collected at 1 week, 1 month, 6 months, 1 year, and thereafter yearly. Acute complications were defined as those occurring within the first month. Chronic complications were those that persisted beyond 6 months. Acute complications were observed in 18% of patients and included hematomas that required drainage, an infection treated with antibiotics, and erythema. Chronic complications were observed in 12% of patients and included a seroma, fibrosis and hyperpigmentation. The majority of acute and chronic problems were mild (Grade I). If Grade I erythema, fibrosis, and hyperpigmentation are not included, only 11/146 patients (7.5%) had significant complications. The rate of acute and chronic complications from X‐ray IORT in DCIS patients was low compared to historical toxicity rates observed in DCIS patients treated with whole breast irradiation. Our data indicate that X‐ray IORT can be utilized safely in patients diagnosed with DCIS.